Global mobile commerce strategies, implementation and case studies - Huang 1964-; Wang; Day (Information Science Reference, 2008)
"This book provides a complete set of in-depth research investigations on global m-commerce strategies and technological standards, as well as case studies on the subject that elucidate the research through real-world examples. It will prove to be a valuable reference to drive the current and future activities of academic researchers and practitioners alike"--Provided by publisher.